2016
DOI: 10.4236/sm.2016.63012
|View full text |Cite
|
Sign up to set email alerts
|

Secrets in the Classroom: Self-Disclosure about Sexual Abuse

Abstract: This paper examined the self-disclosures of students about sexual abuse and assault in a university classroom. These self disclosures were secrets that prevented students from knowing and understanding their deeper selves. We described the structure of a university classroom that encouraged the revelation of secrets in the classroom. The self reported feelings of the seven individuals who revealed secrets, as well as interviews and web posts about the consequences for each individual were the basis of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Specific contexts can encourage young people to reveal their secrets to friends. In particular, Gerrish, Philyaw, Payne, Rabow, and Brar (2016), in a qualitative study, found that some classroom environmental, intrapersonal and relational factors could facilitate the disclosure of secrets. When there are trusting relationships among classmates, the classroom setting can be perceived as a safe place in which to share their secrets.…”
Section: Keeping Secrets From Friendsmentioning
confidence: 99%
“…Specific contexts can encourage young people to reveal their secrets to friends. In particular, Gerrish, Philyaw, Payne, Rabow, and Brar (2016), in a qualitative study, found that some classroom environmental, intrapersonal and relational factors could facilitate the disclosure of secrets. When there are trusting relationships among classmates, the classroom setting can be perceived as a safe place in which to share their secrets.…”
Section: Keeping Secrets From Friendsmentioning
confidence: 99%